[Letter], Bida, N. Nigeria, [to] Mr. Baylis - Macintyre, J. L. (Adam Matthew Digital, 1909)
Ms. letter from J.L. Macintyre to Rev. F. Baylis concerning administrative matters of the Northern Nigeria Mission and particularly personnel matters. An account of the Rev. Low's actions in response to the revolt against the British Resident and other Europeans at Gussuro, near Guta, in the Gwari region, is included